Pink around the rink - Kann, Victoria (New York, N.Y. : HarperCollins, 2010)
Pinkalicious's new ice skates are plain white, so before she takes them out on the ice she decides to color them with her cotton candy pink magic marker.
Keywords: Skating -- Juvenile fiction; Pink -- Juvenile fiction; High interest-low vocabulary books